Pengaruh Rekrutmen Dan Seleksi Terhadap Kinerja Karyawan Pada PT. Bima Sakti Logistik Di Jakarta Timur - Dinda Nurhaliza; Rini Septiowati (Kampus Akademik Publiser, 2026)
Abstract. The purpose of this study is to examine the effect of recruitment and selection on employee performance at PT. Bima Sakti Logistik, East Jakarta. This study employs a quantitative method with an associative approach. The sampling technique used is saturated sampling, involving 58 respondents. Data analysis techniques include validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results show that recruitment has a significant effect on employee performance, with a coefficient of determination of 19.6% and hypothesis testing indicating that the calculated t value > t table (3.695 > 1.672). Selection also has a significant effect on employee performance, with a coefficient of determination of 33.9% and a calculated t value > t table (5.356 > 1.672). Simultaneously, recruitment and selection have a significant effect on employee performance, as indicated by the regression equation Y = 14.086 + 0.158X₁ + 0.476X₂. The coefficient of determination is 36.2%, while the remaining 63.8% is influenced by other factors. Hypothesis testing shows that the calculated F value > F table (15.625 > 3.16).